IMPLEMENTATION OF THE ENVIRONMENTAL SERVICE SUPERVISION SYSTEM FOR MINE C MINING IN THE BOTTOLAI ENVIRONMENT, COPPO VILLAGE, BARRU REGENCY - Dian Pratiwi; Mukmin Muhammad; Muh. Lutfi (Sean Institute, 2023)
This study aims to find out: Implementation of the Supervision of the Environmental Service related to the C Mining C mining in the Bottolai environment and what factors are the obstacles of the Environmental Service to conduct supervision. Data sources are obtained by surveying, interviewing, observation, and documentation. Data analysis uses data reduction, data presentation and drawing conclusions using qualitative methods. The results of this study indicate that the Supervision System of the Environmental Service related to the C mining mine in the Bottolai environment has not been running optimally due to there are still violations that occur in the field. The supervision carried out by the Environment Agency includes pre -operational supervision, operational supervision and post -operational supervision. While the obstacle factors from the Department of Environment in conducting supervision include the distance between the location of the mine and the mining office, there is another busyness from the mining office and the appeal of the acceleration of the development of the railroad tracks.